Novel Technique for Link Recovery in Mobile Ad hoc Networks - Patel, Rajesh Kumar; Singh, Saurabh; Sinha, Kaushal (International Journal of Computer Sciences and Engineering, 2025)
The mobile ad hoc networks is the decentralized type of network in which mobile nodes can join or leave network when they want. Due to such nature of the network security and quality of service are the major issues. This research work is based on quality of service in the network. The AODV is the efficient routing protocol for the path establishment from source to destination. Due to movement of the mobile nodes, link failure may occur which reduce network performance. In this research work, AODV protocol will be further improved which recover path in case of link failure from source to destination. The proposed protocol is implemented in NS2 and simulation results show high performance of proposed algorithm as compared to existing algorithm